Bidentate Hydroxyalkyl NHC Ligands for the Copper‐Catalyzed Asymmetric Allylic Substitution of Allyl Phosphates with Grignard Reagents. Issue 4 (19th December 2012) - Magrez, Magaly; Le Guen, Yann; Baslé, Olivier; Crévisy, Christophe; Mauduit, Marc
<x xml:space="preserve">Abstract</x> Demonstrating their potential: Bidentate alkoxy NHC ligands have been used in the copper‐catalyzed asymmetric allylic alkylation of allyl phosphates with Grignard reagents (see scheme). The method provides access to tertiary and quaternary chiral centers with high regio‐ and enantioselectivity. The system is also applied to the synthesis of chiral E, E‐dienes, a key structural motif prevalent in natural products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>